Peasant scenes and landscapes : the rise of pictorial genres in the Antwerp art market - Silver, Larry, 1947- (University of Pennsylvania Press, 2006)
Larry Silver investigates the origins of new pictorial types and their media as a phenomenon of sixteenth-century Antwerp and interprets several pictorial genres as he charts their evolution and their role in the development and marketing of individual artistic styles.